Development of the Behavioral Inflexibility Scale for Children with Autism Spectrum Disorder and Other Developmental Disabilities. Issue 3 (6th January 2020) - Lecavalier, Luc; Bodfish, James; Harrop, Clare; Whitten, Allison; Jones, Desiree; Pritchett, Jill; Faldowski, Richard; Boyd, Brian
Abstract : Behavior inflexibility (BI) refers to rigid patterns of behavior that contrast with the need to be adaptable to changing environmental demands. We developed a parent‐reported outcome measure of BI for children with autism spectrum disorder (ASD) and other developmental disabilities with a multi‐step iterative process. A pool of 62 candidate items was generated through expert panel feedback, review of existing scales and focus groups. A consensus process was used to generate the final 38 items. Parents of 943 children (age range, 3–18 years; average, 11.4 years; 79% boys) with ASD completed an online survey. One hundred thirty‐three parents rated their child twice within 3 weeks (average = 16.5 days). A series of factor analyses suggested that the 38 items measured a single construct. Scores had a weak correlation with level of functioning (−0.12) and did not differ based on sex. Scores had a negligible correlation with age (−0.07), although measurement invariance was not supported. The mean total score for the Behavioral Inflexibility Scale (BIS) was normally distributed. Internal consistency was α = 0.97 and temporal stability was r = 0.92. Correlations with parent ratings on the subscales of the Repetitive Behavior Scale—Revised varied from 0.48 to 0.89. The correlation with parent ratings on the Social Communication Questionnaire total score was 0.52. Our data show that BI in children with ASD ranges significantly from mild to severe and that the 38‐item BIS is valid and reliable. Autism Res 2020, 13: 489–499 . © 2020 The Authors. Autism Research published by International Society for Autism Research published by Wiley Periodicals, Inc. Lay Summary: We developed a parent‐completed rating scale of behavior inflexibility (BI) for children with developmental disabilities using a multistep process. The Behavioral Inflexibility Scale (BIS) contains 38 questions rated on a 6‐point scale. Parents of 943 children with autism spectrum disorder (ASD) completed an online survey. We examined associations between the BIS and other scales and demographic variables. The BIS is valid and reliable. BI in children with ASD ranges from mild to severe.